Effects of terpenes in the treatment of visceral leishmaniasis: A systematic review of preclinical evidence. (March 2022) - Raimundo, Vagner Dias; Carvalho, Renner Philipe Rodrigues; Machado-Neves, Mariana; Marques-da-Silva, Eduardo de Almeida
Abstract: Visceral leishmaniasis (VL) is a severe and potentially fatal neglected tropical disease, being considered a public health concern in many countries worldwide. There are still no vaccines against human VL, and the existing chemotherapy is often toxic. Thereby, alternative treatments have been investigated, and byproducts from plant metabolism have been a source of promising pharmacological compounds. Terpenes are secondary metabolites that exhibit a large spectrum of therapeutic activities. Herein, we conducted a systematic review to evaluate the effects of terpenes in the treatment of VL in rodents. After an extensive search using the PubMed/MEDLINE, Scopus, and Web of Science databases, we included 34 articles in this review. Our results revealed that triterpenes were the most used terpenes by the eligible studies. Overall, terpene treatment showed no or negligible toxicity, causing an increase in the Th1-type immune response profile and nitric oxide production. It also reduced the Th2 cytokines levels and parasite load (> 90% to > 99%). Moreover, terpenes induced apoptosis by damaging the plasma membrane and inhibiting DNA topoisomerases in the parasite. The use of terpene carriers increased the terpene bioavailability in the body, preventing their rapid excretion and promoting the drug delivery at the site of Leishmania infection. Terpene derivatives showed better pharmacokinetics than the original terpenes. Altogether, the benefits of VL treatment with terpenes in preclinical studies may open new directions for other preclinical and human trials. Graphical Abstract: Schematic representation of the effects triggered by the administration of terpenes after the treatment of murine models infected with VL. The works showed that terpenes exhibit negligible toxicity during therapy and are capable of directly killing the parasites by acting on their plasma membranes or other components, such as the DNA-topoisomerase enzyme, culminating in apoptosis. Terpenes were also able to kill them indirectly due to the effects of these compounds in modulating the immune response, in which they promoted an improvement in the Th1 immune response, increasing the cytokines of this immune response profile (IFN-γ, TNF-α and IL -12), and decreasing the Th2 immune response, causing a decrease in the cytokines of this immune profile (IL-4, IL-10 and TGF-β). Both the direct and indirect effects of terpenes on the parasites promoted a reduction in the parasite load in the main affected organs (spleen and liver). ga1